2023
DOI: 10.3390/su15054079
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Local Carbon Emission Reduction: Evidence from Guangdong, China

Abstract: Based on the data obtained on carbon emissions in Guangdong Province, China, from 1997 to 2019, this study focused on the relationship between energy consumption and population development in Guangdong Province. This study quantitatively analyzed the impact of different population structures and technological progress on carbon emissions in Guangdong Province by establishing an extended model of Stochastic Impacts by Regression on Population, Affluence, and Technology (STIRPAT). The results showed that the pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…In light of the effects of population elements on per-capita carbon emissions, we advocate reverting to the traditional household structure and a large family. Previous research has noted that the decline in household size and the increase in the number of households will cause a rise in the demand for durable consumer items and basic household essentials, boosting carbon emissions 25 , and a similar finding was obtained in this investigation. We can therefore start by expanding household size and formulate policy proposals to indirectly reduce per-capita carbon emissions.…”
Section: Act According To Local Conditionssupporting
confidence: 89%
See 2 more Smart Citations
“…In light of the effects of population elements on per-capita carbon emissions, we advocate reverting to the traditional household structure and a large family. Previous research has noted that the decline in household size and the increase in the number of households will cause a rise in the demand for durable consumer items and basic household essentials, boosting carbon emissions 25 , and a similar finding was obtained in this investigation. We can therefore start by expanding household size and formulate policy proposals to indirectly reduce per-capita carbon emissions.…”
Section: Act According To Local Conditionssupporting
confidence: 89%
“…In addition, the link between population-related factors and carbon emissions has remained a considerable topic of interest. The STIRPAT model can be employed to quantify the effects of population-related factors on carbon emissions, and the findings revealed that various factors can produce unique effects, both positive and negative 25 . Therefore, more notably, considering population-related factors is necessary when examining carbon emissions based on population.…”
Section: Spatiotemporal Differences In and Influencing Effects Of Per...mentioning
confidence: 99%
See 1 more Smart Citation
“…From an industrial perspective, formulating differentiated subsidy programs [29], improving reward and punishment mechanisms [30], and establishing governance mechanisms shared by stakeholders [31] can promote the green transformation of various industries and achieve carbon emission reduction policy goals. The literature above shows that the stakeholders in the government's administrative emission reduction are mainly the manufacturing industry, which emits carbon emissions, while ignoring a basic variable in social and economic activities-citizens [32]. From a macro perspective, demographic characteristics, such as the working-age population, family size, and educational level, have an increasingly significant impact on carbon emissions [33].…”
Section: Carbon Reduction Policy Researchmentioning
confidence: 99%
“…This is essential for understanding time-sensitive events and identifying interactions over time. The DCCE estimator will assist in addressing endogeneity and autocorrelation concerns in certain scenarios (Wen et al, 2023). The DCCE estimator was selected since it deals with the unobserved standard shocks using the CCE and controls the endogeneity issue (Edziah et al, 2022).…”
Section: Data Processingmentioning
confidence: 99%